Let S 1 , S 2 , S 3 denote the sums of the first n positive integers, their squares, and their cubes respectively. Find
( S 2 ) 2 S 3 ( 1 + 8 S 1 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Just forgot the square in denominator
Log in to reply
EXACTLY ! :(
Same here :/
nice solution.!
Take n=1, s1= s2= s3= 1. so the value of expression= 9
You also need to check n=2 so that it isn't "depends on n."
From this you can't possibly know how it will behave if you take, e.g. 1029314203, you have to know how it behaves on n, the best way to do this is through the already well-known sums for the natural numbers, square of natural numbers e cubes of natural numbers. They're easily proven to work on any n ∈ N , using induction.
superb genius
Use the direct formulas for the sum of first n numbers, sum of squares of first n number and sum of cubes of first n numbers. This will give answer straightaway.
Now, can this be solved if we dont remember the formulas? Yes we can. Becasue this is a multiple choice qn, trial and error is an appropriate method.
Now, let the numbers be the first 3 natural numbers (1,2,3)
Then we get,
S1= 1+2+3 = 6.
S2 = 1+4+9 = 14,
S3 = 1+8+27 = 36.
Now putting these values in
( S 2 ) 2 S 3 ( 1 + 8 S 1 ) = 9
Now to be sure of the answer, try with a different pattern. Take the first 5 natural numbers (1,2,3,4 and 5)
Then we get,
S1= 1+2+3+4+5 = 15.
S2 = 1+4+9+16+25 = 55,
S3 = 1+8+27+64+125 = 225.
Now putting these values in
( S 2 ) 2 S 3 ( 1 + 8 S 1 ) = 9
So, the answer is 9
I. Did the same
s3=(s1)^2; s2=s1(2n+1)/3
Plugging in the values we get the answer=9
Straightforward using a computer symbolic algebra software, in this case the Python sympy library:
1 2 3 4 5 6 7 8 9 10 11 12 13 14 |
|
Problem Loading...
Note Loading...
Set Loading...
We know that :
S 1 = 2 n ( n + 1 )
S 2 = 6 n ( n + 1 ) ( 2 n + 1 )
S 3 = 4 n 2 ( n + 1 ) 2
Just plug in the values to get :
= ( 6 n ( n + 1 ) ( 2 n + 1 ) ) 2 4 n 2 ( n + 1 ) 2 ( 1 + 8 2 n ( n + 1 ) )
= 9